Effects of Acetone Extract of Green Tea (Camellia sinensis) on Diameter, Viability, and Germinal Vesicle Breakdown Rate of Zebrafish Oocytes (Danio rerio) Exposed to Heat Stress as an Animal Model - Tuska, Habib Syaiful Arif; Hidayah, Aaliyah Nurul; Lonameo, Bonick Kartini; Bello, Umar; Budiono (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
Global warming is characterized by increasing temperatures of the earth's atmosphere, ocean and land, resulting in extreme climate change. The effects of climate change will affect animal health through increased ambient temperature (heat stress). This study using Zebrafish as animal model like our previuous study because Zebrafish, have 70% identical genetic similarity to humans. In addition, Zebrafish have specific approval from the U.S. Food and Drug Administration for new drug discovery research. Heat stress negatively affects animal health through an increase in Reactive Oxygen Species (ROS), especially in the reproductive system because it causes a decrease in reproductive efficiency, such as follicular development, oocyte quality, and oocyte maturation. Antioxidant supplementation, namely green tea extract, is needed to reduce the negative effects of heat stress. The purpose of this study was to analyze the difference of 4 µl dose of green tea extract (Camellia sinensis) on the diameter, viability, and Germinal Vesicle Breakdown (GVBD) rate of Zebrafish oocytes at normal temperature (28℃) and with exposure to heat stress (32℃; 34℃). Zebrafish oocytes were collected and grouped into 2 (two) treatment groups including, non-heat stress group (28℃) and heat stress group (32℃; 34℃) with 6 repetitions. Quantitative data were processed using SPSS software with Two Way ANOVA analysis. The results of Two Way ANOVA showed that green tea extract supplementation had a positive effect on the diameter, viability, and GVBD of Zebrafish oocytes. This is indicated by the significance of the percentage of diameter (P=0.002), viability (P=0.003), and GVBD rate (P=0.000).